The Asian Multi-City Epidemiology Work Group South Asia (11 - 16 April 1994) East Asia (8 - 12 August 1994). - Navaratnam, Profesor Madya (Dr.) V.; Foong, Dr. , Kin; Tan, Bee Leng (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1994)

(untitled)
As there is no compulsory reporting system in respect of drug abuse in the country at present / the number of abusers of different substances is not possible to be determined. An event reporting system called Drug Abuse Monitoring System (DAMS) was established recently by the National Dangerous Drugs Control Board with UN assistance.